PERLINDUNGAN HUKUM TERHADAP PELAKU USAHA AKIBAT PEMBATALAN SEPIHAK OLEH KONSUMEN DALAM JUAL BELI ONLINE MELALUI SISTEM CASH ON DELIVERY (STUDI PENELITIAN DIKOTA MEDAN) - fadil, muhammad; yulia, Yulia; kurniasari, Tri widya (Jurnal Ilmiah Mahasiswa Fakultas Hukum Universitas Malikussaleh, 2025)
Nowadays, online buying and selling transactions are an option that is very popular with the public because of its convenience and benefits. In these transactions there are also many payment methods in online buying and selling, one of which is cash on delivery (COD), however, in this cash on delivery payment method, many business actors experience losses as a result of unilateral cancellations made by consumers. Therefore, this research aims to find out the mechanism for cash on delivery as well as legal protection for business actors due to unilateral cancellations by consumers in online buying and selling through the cash on delivery system. The method in this research uses empirical juridical research which is often called sociological legal research or field research. This research links law with real human behavior. The results of this research are online buying and selling transaction mechanisms in the cash on delivery payment system. When placing an order, consumers are required to make payment first before opening and viewing the product ordered so that the consumer cannot cancel it. If the consumer feels it is not suitable for the product, the consumer can returning the product to the business actor.  Legal protection for business actors is inadequate due to the lack of good faith by consumers in canceling online buying and selling transactions using the cash on delivery payment system and there are no sanctions that have been determined if consumers are legally guilty of unilateral cancellation, therefore the need for the government to carry out a review reinstate the Consumer Protection Law or create new regulations specifically for online shopping, especially to protect business actors from consumers who do not have good intentions.